n Stelselontleding van rewolusionere aktiwiteite - Van der Merwe, C. Johannes(Christoffel Johannes) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Phil.) -- Universiteit van Stellenbosch, 1980.